CHRONICLING THE MEROVINGIANS IN HEBREW: THE EARLY MEDIEVAL CHAPTERS OF YOSEF HA-KOHEN'S DIVREI HAYAMIM. (2019) - FOX, YANIV
Abstract : Yosef Ha-Kohen (1496–ca. 1575) was a Jewish Italian physician and intellectual who in 1554 published a chronicle in Hebrew titled Sefer Divrei Hayamim lemalkei Tzarfat ulemalkei Beit Otoman haTogar, or The Book of Histories of the Kings of France and of the Kings of Ottoman Turkey . It was, as its name suggests, a history told from the perspective of two nations, the French and the Turks. Ha-Kohen begins his narrative with a discussion of the legendary origins of the Franks and the history of their first royal dynasty, the Merovingians. This composition is unique among late medieval and early modern Jewish works of historiography for its universal scope, and even more so for its treatment of early medieval history. For this part of the work, Ha-Kohen relied extensively on non-Jewish works, which themselves relied on still earlier chronicles composed throughout the early Middle Ages. Ha-Kohen thus became a unique link in a long chain of chroniclers who worked and adopted Merovingian material to suit their authorial agendas. This article considers how the telling of Merovingian history was transformed in the process, especially as it was adapted for a sixteenth-century Jewish audience.